Relation between ambient humidity and ionic conductivity of poly(thionaphtheneindole): Behaviour as an amperometric humidity sensor - CasalboreMiceli, G.; Camaioni, N.; Beggiato, G.; Campos, M.; Mari, C. M. (Chapman Hall Ltd, 1997)
The electrical characteristics of oxidized poly(thionaphtheneindole) were investigated as a function of ambient relative humidity (r.h.). The current flowing through a pressed pellet of material between two massive gold electrodes plotted against voltage gives a wave-shaped curve with a halfwave potential at V = similar to 3 V. The current recorded at 4 V (plateau of the wave) is a sigmoidal function of r.h, with the inflexion point at similar to 60%. An interpretation of these findings is given, based on the influence of water on the dielectric constant of the material and on acid-base equilibrium between poly(thionaphtheneindole) and water, from which protons are produced. The behaviour of poly (thionaphtheneindole) as the active component of an amperometric humidity sensor is also reported.